Urinary Metalloproteinases-9 and -2 and Their Inhibitors TIMP-1 and TIMP-2 are Markers of Early and Long-Term Graft Function After Renal Transplantation - Ewa Kwiatkowska; Leszek Domanski; Joanna Bober; Krzysztof Safranow; Maciej Romanowski; Andrzej Pawlik; Sebastian Kwiatkowski; Kazimierz Ciechanowski (Kidney & Blood Pressure Research, 2016)
Background/Aims: Renal ischemia-reperfusion (I-R) injury (IRI) is an inseparable feature of organ transplantation and may have a negative impact on the graft, its function and survival. Acute tubular necrosis, which is reversible thanks to the regenerative capacity of renal tubular epithelial cells, is the main cause of acute renal failure secondary to IRI. MMP-2 and MMP-9 are proteolytic enzymes involved in digesting proteins that are components of the extracellular matrix (ECM) and the basement membrane of the nephrons. This way post-reperfusion MMP activation allows the inflammatory process to spread. Methods: In our studies, we focused on identifying whether the concentrations of MMP-2 and MMP-9 and their natural inhibitors TIMP-1 and TIMP-2 in urine sample at day 1 and day 30 as well as after 12 months following renal transplantation are markers of early and long-term renal function during meanly five-years observation. Moreover, in urine sampled at months 6 and 12 after renal transplantation, we determined the content of TGF-β as a graft fibrosis indicator. Results: MMP-9 concentration in the early post-transplant period is a major marker of early and long-term function of the transplanted kidney. Its increased concentration was correlated with lesions related to tubular atrophy and fibrosis in renal biopsies performed at months 3 and 12 after transplantation. Its concentration is correlated with TGF-β content in a later period. Conclusions: TIMP-1 and-2 are primarily markers of an early function of the transplanted kidney. Early post-transplant concentration of MMP-2 is a marker of proteinuria in early and long-term post-transplant periods.